2019
DOI: 10.3847/1538-4357/ab107c
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Sample: The Relationship between the Black Hole Mass of BCGs and the Total Mass of Galaxy Clusters

Abstract: Supermassive Black Holes (BHs) residing in brightest cluster galaxies (BCGs) are overly massive when considering the local relationships between the BH mass and stellar bulge mass or velocity dispersion. Due to the location of these BHs within the cluster, large-scale cluster processes may aid the growth of BHs in BCGs. In this work, we study a sample of 71 galaxy clusters to explore the relationship between the BH mass, stellar bulge mass of the BCG, and the total gravitating mass of the host clusters. Due to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
(109 reference statements)
0
15
0
Order By: Relevance
“…Indeed, in their Table 4 they report σ M BH |M BCG = 0.61 and σ M BH |T = 0.38. The values of the scatters increase in the later analysis by Phipps et al (2019) because of the method used to derive M BH , the authors suggest. Despite, also in that case the two intrinsic scatters in M BH are comparable between each other.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, in their Table 4 they report σ M BH |M BCG = 0.61 and σ M BH |T = 0.38. The values of the scatters increase in the later analysis by Phipps et al (2019) because of the method used to derive M BH , the authors suggest. Despite, also in that case the two intrinsic scatters in M BH are comparable between each other.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, a few simulated galaxies were identified in Horizon-AGN with M bulge 10 12.5 M , i.e. more massive than the observed ones (Bogdán et al 2018;Phipps et al 2019), and overmassive with respect to their M 500 . These simulated galaxies could be too massive while providing a good agreement for the mass of their BHs.…”
Section: Bhs In Massive Galaxies Of M 10 12 Mmentioning
confidence: 95%
“…The most massive BHs reside in BCGs with bulge mass up to M bulge < 10 12.5 M . A non-negligible fraction of the BHs residing in BGGs and BCGs are overmassive with respect to the bulge stellar mass or the stellar velocity dispersion of their host galaxies (Bogdán et al 2018;Phipps et al 2019), compared to the scaling relation of McConnell & Ma (2013) for example. In the comparison of Bogdán et al (2018) with the Horizon-AGN simulation, a very good agreement is found in the plane M BH − M 500 (M 500 the mass enclosed in a sphere of mean mass density 500 times the Universe critical density).…”
Section: Bhs In Massive Galaxies Of M 10 12 Mmentioning
confidence: 99%
“…A few rare objects, e.g., NGC4342 and NGC4291, appear to have become overly "enthusiastic", at early epochs, and may have terminated star formation before the stellar mass grew to the characteristic size needed to lie on the stellar mass -SMBH mass relation. New scaling relations (e.g., Bogdán & Goulding 2015;Bogdán et al 2018;Phipps et al 2019, andGaspari et al 2019) suggest that the stellar mass may not be the fundamental driver of SMBH mass. X-ray all-sky surveys from eROSITA will provide large samples of X-ray bright galaxies to fully explore the present epoch population of dark matter halos and their hot gas content.…”
Section: Discussionmentioning
confidence: 99%